Environmental Risk and Protective Factors and Their Influence on the Emergence of Psychosis - A. Schlosser, Danielle; Pearson, Rahel; B. Perez, Veronica; L. Loewy, Rachel (Adolescent Psychiatry, 2012)
Environmental risk and protective factors in schizophrenia play a significant role in the development and course of the disorder. The following article reviews the current state of evidence linking a variety of environmental factors and their impact on the emergence of psychotic disorders. The environmental factors include pre- and perinatal insults, stress and trauma, family environment, and cannabis use. The review of evidence is followed by case examples and clinical applications to facilitate the integration of the evidence into clinical practice.
Keywords: environmental factors